Odpowiedzi

2010-02-14T17:57:09+01:00
A. -4x-7-3x+7=-7x
b. x-2xy+1/2x-1/3xy=1 1/2x -2 1/3xy
c. -x²+y²-2y²=-x²-y²
d. -x²+2x-3x+x²=-x
e. 4x+4-7x-1/2=-3x+3 1/2
f. -2ab+12a-4ab-16a=-6ab-4a
21 4 21
2010-02-14T17:58:15+01:00
A. -4x-7-3x+7 = -7x
b. x-2xy+1/2x-1/3xy = 1 1/2x - 2 1/3xy
c. -x²+y²-2y² = -x² - y²
d. -x²+2x-3x+x² = -x
e. 4x+4-7x-1/2 = -3x + 2 1/2
f. -2ab+12a-4ab-16a = -6ab - 4a
21 3 21
2010-02-14T18:00:02+01:00
A)
-4x-7-3x+7=-4x-3x+7-7=-7x
b)
x-2xy+1/2x-1/3xy= 1¹/₂x - 2¹/₃xy
c)
-x²+y²-2y²=-x²-y²
d)
-x²+2x-3x+x²=x²-x²+2x-3x=-x
e)
4x+4-7x-1/2=4x-7x+4-¹/₂=-3x+3¹/₂
f)
-2ab+12a-4ab-16a= 12a-16a-4ab-2ab=-4a-6ab
26 4 26